Perspective of Secondary School Students in Relation to the Preparation of Research Reports during the Year 2022 - Ureña Hernández, Mariam (2023)
This research aimed to know the perspective of high school students regarding the preparation of research reports and all those aspects related to format, resources and participation in projects and activities carried out at the national level in the country’s technical high schools, which seek educational and professional growth through research and the creation of proposals. The research was conducted under a qualitative approach of an exploratory and descriptive type, with the participation of 98 students from three technical high schools, who study the specialties of Executive Secretariat, Accounting, and Tourism. Aspects such as the frequency with which they carry out research, the format, topics of interest, obstacles, and frequent errors when carrying out research, as well as the educational and personal resources they have were consulted. The result was that, for the students, it is important to investigate and they project themselves as technological researchers who take advantage of the applications and the ease of searching for instant and free information, who are knowledgeable about the format and writing regulations but face obstacles such as little intrinsic and extrinsic motivation, the lack of soft skills necessary to work as a team, and the lack of knowledge in the research process.